2015
DOI: 10.1016/j.pop.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy

Abstract: The prevalence of diabetes is on the rise globally as are the consequences, such as diabetic retinopathy. Diabetic retinopathy is a leading cause of vision loss in working-age adults in developed countries. Visual impairment as a result of diabetic retinopathy has a significant negative impact on the patient's quality of life and their ability to successfully manage their disease. Glycemic control, blood pressure normalization, and lipid management form the basis for long-term diabetes management and protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
150
0
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 23 publications
1
150
0
15
Order By: Relevance
“…This complication is a result of multiple pathogenic processes caused by hyperglycemia and the deregulation of insulin signalling pathways, which in turn causes neuro-retinal dysfunction and retinal microvascular degeneration (2,3). The early clinical signs of DR include microaneurysms and hemorrhages, while the later signs are narrowed, tortuous and irregular retinal blood vessels, due to the formation of abnormal new blood vessels at the back of the eye in proliferative DR (4).…”
Section: Introductionmentioning
confidence: 99%
“…This complication is a result of multiple pathogenic processes caused by hyperglycemia and the deregulation of insulin signalling pathways, which in turn causes neuro-retinal dysfunction and retinal microvascular degeneration (2,3). The early clinical signs of DR include microaneurysms and hemorrhages, while the later signs are narrowed, tortuous and irregular retinal blood vessels, due to the formation of abnormal new blood vessels at the back of the eye in proliferative DR (4).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of DR, a leading cause of vision loss, has risen globally, resulting in negative impacts on patient life quality (Hendrick et al 2015). Studies have demonstrated that miRs play an important role in the pathogenesis of diabetes and the related micro-and macrovascular complications (Mastropasqua et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As hemorragias intra-retinianas são lesões vermelhas maiores e mais irregulares ocorridas na retina, que geralmente desaparecem depois de 3 a 4 meses. Já os exsudatos são lesões de aspecto amarelado, resultado de deposição de lipídeos e proteínas na retina [4].…”
Section: Introductionunclassified
“…As hemorragias intra-retinianas são lesões vermelhas maiores e mais irregulares ocorridas na retina, que geralmente desaparecem depois de 3 a 4 meses. Já os exsudatos são lesões de aspecto amarelado, resultado de deposição de lipídeos e proteínas na retina [4].Quanto mais cedo for detectado da RD, mais chance o paciente tem de retardar a progressão da doença, e assim, diminuir as chances de o paciente ficar cego. O diagnóstico manual requer muito esforço do especialista em oftalmologia para detectar as características que indicam a presença de RD.…”
unclassified